French writers in the face of anti-semitic language under nazioccupation: Edith Thomas, Antoine de Saint-Exupery - Mamatsashvili, Atinati (Romanica Olomucensia, 2017)
According to Victor Klemperer, Nazi language often used borrowed words but the danger lies in the transformation they undergo once they are transferred into "general language". This study aims to focus on the anti-Semitic language adopted and manipulated by the Vichy regime to reveal the extent to which the new language is offered as a "new way" of thinking (Klemperer). To do this, we refer to the works of writers who particularly stressed the threat of the simultaneous alteration of language and thought in the grip of authoritarian and anti-Semitic regimes. It is dealt with here through a focus on Pilote de guerre (1942) by Antoine de Saint-Exupery and Journal intime de Monsieur Celestin Costedet (written between 1940 and 1941) by Edith Thomas.
Keywords: Nazi occupation; anti-Semitism; Jews; stereotypes; French literature